Pair replacement on the spawning success of broodstock Seahorse (Hippocampus barbouri) - Syafiuddin, .; Junior, M. Zairin; Jusadi, Dedi; Carman, Odang; Affandi, Ridwan (Jurnal Akuakultur Indonesia, 2011)
Seahorse, (Hippocampus barbouri) is one of marine living resources having high commercial values and has commonly been traded especially as live ornamental aquarium fish, raw material of traditional medicine and as souvenirs. This expriment was conducted to determine the succces of spawning rate by replacing the broodstock pair of seahorse. This study was done experimentally with treatment of replacement of broodstock pair after spawning under control condition. The experiment was designed to apply completely randomize design by using the following treatments: Treatment A, without replacement neither male nor female. Treatment B, spawned female broodstock  was being mated with her unpaired male broodstock.  Treatment C, a male broodstock that still brood was being mated with his unpaired female broodstock.  Treatment D, a spawned male broodstock that has released larva was being mated with his unpaired female broodstock.  Results showed that under control condition the replacement of broodstock pairs of seahorse had significantly influenced the spawning interval, number of eggs released and number of juveniles produced (P0,05).  It can be concluded that seahorse is not monogamous, either male or female after being spawned may accept other pair for the next spawning. Key words: pair replacement, broodstock, success spawning, Hippocampus barbouri   ABSTRAK Kuda laut, (Hippocampus barbouri) merupakan salah satu sumberdaya hayati laut yang memiliki nilai komersial dan telah banyak diperdagangkan terutama sebagai ikan hias, bahan baku obat tradisional dan juga sebagai suvenir. Penelitian ini dilakukan dengan tujuan untuk mengkaji tingkat keberhasilan pemijahan dengan penggantian pasangan induk kuda laut pada wadah budidaya. Percobaan ini dilakukan secara ekperimental dengan perlakuan penggantian pasangan induk setelah pemijahan dalam wadah budidaya. Percobaan dirancang dengan menggunakan rancangan acak lengkap (RAL) dengan perlakuan sebagai berikut: Perlakuan  A, pemijahan   sepasang  induk kuda laut (tanpa pergantian). Perlakuan B, pemijahan induk betina yang telah memijah dengan induk jantan bukan pasangannya. Perlakuan C, pemijahan  induk  jantan  yang telah memijah (mengerami telur) dengan induk betina bukan pasangannya. Perlakuan D, pemijahan induk jantan yang telah melahirkan dengan induk betina bukan pasangannya. Hasil penelitian menunjukan bahwa penggantian pasangan induk pada wadah budidaya sangat berpengaruh terhadap interval pemijahan, jumlah telur yang dikeluarkan dan jumlah juwana yang dihasilkan (P0,05). Dari hasil penelitian ini disimpulkan bahwa kuda laut, tidak bersifat monogami, artinya baik jantan maupun betina setelah memijah dapat menerima pasangan lain untuk pemijahan berikutnya. Kata kunci: induk, keberhasilan pemijahan, pergantian pasangan, Hippocampus barbouri